(untitled) (Fiep Bulletin - online, 2020)
Summary: Interclass games are sporting events that work on the physical, mental and social aspects of their participants. They happen within the school with disputes between students of different grades and different classes, with a common goal among participants: to be the winner of this modality. They are generally related to sports, but it depends on the school’s goal along with the teachers’, and besides sports they may include grammar, math, board games and popular games. be included to the full, proposing changes to the school’s PPP and physical education teacher lesson planning. The methodology aims to establish literature review and critical analysis of scientific articles. For each of them, individually, a critique will be conducted based on a questionnaire organized by Cunha (2015). Souza’s studies (2018) show the possibility of working with competitive games and manifestations of these games at school. Souza et al. (2018) have good points for reflection and thought, reporting in practice how interclass games are performed, and thus the extent to which they can arrive can be observed. Melchiades e Silva (2016) demonstrate the importance that sports competitions have in the development of a student while belonging to basic education. Interclass games are resources of a methodology that is already used and shows how its permanence until today in the school environment. It is a strategy that differentiates learning in physical education from the standard method of lessons by semester modules, well formulated and included in the school PPP is one of the positive factors for teachers and students in the teaching-learning process.